Knowledge, Attitude, and Practice on Food Safety among Senior High School Students in Jatinangor from AugustâNovember 2013 - Binti Ahamad Naina, Hamizah Sabrina; Kuswardinah, Ine; Dewi, Sumartini (Althea Medical Journal, 2016)
Background: Food safety is defined as the confidence level that food will not cause sickness or harm toÂ consumer when it is prepared, served, and eaten according to its intended use. This study was conductedÂ to describe the pattern of knowledge, attitude, and practice on food safety among high school students inÂ Jatinangor.Methods: One hundred and two respondents were involved in this study. The data were collected fromÂ the high school students in Jatinangor, West Java from August to November 2013 through the methodsÂ of questionnaire after the informed consent was obtained from the respondents. The questionnaire wasÂ translated from the Five Keys to Safer Food Manual by World Health Organization. The collected data wereÂ then presented in percentage.Results: Overall, 60.78% of respondents had moderate knowledge, 85.29% had good attitude, and 71.57%Â had good practice in food safety. Among the five main points on food safety in all aspects, most of theÂ respondents were unaware of the safe temperature to store food; hence, they did not practice it.Conclusions: Even though most of the students have the knowledge, attitude, and practice on food safety,Â a need for relevant and motivating education should be performed for spesific indicators of food safety.Â [AMJ.2016;3(2):206â11]DOI:Â 10.15850/amj.v3n2.797